Contemporary corporate finance - McGuigan, James R.; Moyer, R. Charles 1945-; Rao, Ramesh K. S.; Kretlow, William J. (South-Western, Cengage ‪Learning, 2012)
Gives students an introduction to financial management focusing on maximizing shareholder wealth and effectively managing cash flow. This title places the same financial analysis tool used daily by Wall Street professionals into the hands of students to further their financial management skills and success.